Balancing Offshore Wind Development with Wildlife and Habitat Conservation in the Gulf of Maine - Donoghue, Eliza (Maine Policy Review, 2023)
The potential for offshore wind energy development using floating technology in the Gulf of Maine is enormous. Development in the Gulf of Maine – which boasts some of the highest sustained wind speeds in the world that peak in the winter when Maine’s energy needs are the greatest – stands to play a big part in solving our climate puzzle. However, this opportunity must be considered alongside the known and potential negative impacts to Gulf wildlife, fish, and marine habitats. Maine Audubon biologists and policy experts are confident that with meaningful investments in research and monitoring, adaptive management, and the adoption of state and federal policy tools, the benefits to wildlife from offshore wind development outweigh the risks. Climate change is the greatest threat to wildlife in Maine and we must thoughtfully embrace technologies that will lessen that threat.